Community Collage Service (KKN) Student Assistance to Improve Women's Health by Detecting Breast Cancer and Cervical Cancer in Amansari Village, Karawang Regency - Dini Widianti; Yusnita Yusnita; Rita Komalasari (Journal of Community Empowerment for Health, 2022)
Introduction: KKN (Community Collage Service) is an activity that is followed by students to be able to recognize and interact with the community directly and can be agents of change in the region. Amansari village only has a sub-district health center with 1 medical staff and 3 midwives, although there are no reports of cervical cancer and breast cancer but with a total of around 4487 women and health workers who are still minimal, training and counseling regarding cervical examination with IVA and BSE training (Breast Self-Check) can be done and realized. The aim of the study was to increase Women's Health Concern by Early Detection of Breast Cancer and Cervical Cancer, which was conducted by lecturers and students, namely counseling on early detection of breast cancer with BSE and early detection of cervical cancer with IVA examination. Method: The activity is carried out through stakeholder socialization stages, data collection on knowledge level about breast cancer and cervical cancer for 1 week, then respondents are also given information on IVA examination and how to do BSE, then implementation by mentoring by trained lecturers and midwive and free for women in Amansari district. Results: The results obtained an increase in knowledge from 60 respondents who attended counseling the value of pretest 45.5 and posttest value 59, of the 20 respondents who did IVA and BSE examination there were 2 people suspected of cervical abnormalities and 2 people there were lumps in the breast the respondent was given a referral to the primary health care. Conclusion: The activities carried out have had an impact on increasing the knowledge and skills of early detection of cervical cancer and breast cancer in womans, health workers, cadres and students. BSE skills can be done independently, so that knowledge of women's reproductive health attitudes and behaviors can be better.